2022
DOI: 10.1101/2022.09.20.508228
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A PDLP-NHL3 complex integrates plasmodesmal immune signaling cascades

Abstract: The plant immune system relies on the perception of molecules that signal the presence of a microbe threat. This triggers signal transduction that mediates a range of cellular responses via a collection of molecular machinery including receptors, small molecules, and enzymes. One response to pathogen perception is the restriction of cell-to-cell communication by plasmodesmal closure. We previously found that while chitin and flg22 trigger specialized immune signaling cascades in the plasmodesmal plasma membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Plasmodesmal closure is an early reaction, initiated within 30 minutes upon perceiving pathogen-derived molecules and stress-associated signals including SA and hydrogen peroxide (Xu et al 2017;Cheval et al 2020;Tee et al 2023b), and is critical for the execution of a full response. Thus, we reason that plasmodesmal closure regulates a range of downstream processes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Plasmodesmal closure is an early reaction, initiated within 30 minutes upon perceiving pathogen-derived molecules and stress-associated signals including SA and hydrogen peroxide (Xu et al 2017;Cheval et al 2020;Tee et al 2023b), and is critical for the execution of a full response. Thus, we reason that plasmodesmal closure regulates a range of downstream processes.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we reason that plasmodesmal closure regulates a range of downstream processes. However, considering the plethora of responses elicited during immunity, and the array of elicitors that trigger plasmodesmal closure via converging signaling pathways (Tee et al 2023b) Transcriptional profiling of responses to plasmodesmal closure identified transcriptional signatures of defense responses associated with SA production and signaling. It has long been known that constitutive over-production of the plasmodesmal protein PDLP5 closes plasmodesmata and leads to high levels of SA (Wang et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The level of callose deposition is a highly regulated process involving two antagonistic enzymes, Callose Synthases and β-1,3-glucanases (Chen and Kim, 2009). Callose deposition is enhanced according to two main signalling pathways, one Reactive Oxygen Species (ROS)-dependent and the other one salicylic acid (SA)-dependent, which both induce the expression of receptor proteins such as PDLP5 that participate with Callose Synthase proteins in the regulation of PD permeability (Cui and Lee, 2016; Amsbury et al, 2018; Tee et al, 2022). The expected decrease in PD permeability under H 2 0 2 stress was not observed when FW2.2 is overexpressed, suggesting that FW2.2 play a role in the ROS-dependent pathway.…”
Section: Discussionmentioning
confidence: 99%
“…1 A-H). These bridges are maintained post-cytokinesis and are the foundation for generating a multicellular communication network, indispensable for plant life (3,(10)(11)(12)(13)(14)(15)(16)(17)(18).…”
Section: Main Textmentioning
confidence: 99%